Stability Analysis of Earthen Sites Reinforced with Stabilized Soil Including Calcified Ginger Nuts based on Finite Element Numerical Simulation. Issue 1 (January 2022) - Hu, Xiaoying; Li, Dandan; Peng, Erxing; Chou, Yaling; Li, Qifeng; Dang, Bing
Abstract: The stability of the earthen sites wall of Niutoucheng in Lintan County is studied by using the strength reduction method and finite element analysis software ABAQUS. The stability of the model before and after the reinforcement of the central undercutting wall of the earthen sites was analyzed. The strain distribution and stability safety factor variation before and after reinforcing earthen with calcined ginger nuts are discussed. The results show that the development of plastic strain zone is significantly restrained after reinforcing undercutting zone by using stabilized soil including calcined ginger nuts. The stability safety factor of the earthen sites wall model after the central undercutting presents an increasing trend. The stability safety factor of the model before undercutting is 1.430. The stability safety factor of the model is 1.959 and 1.966 after ramming for 7d and 14d, respectively. The judgment of plastic strain zone development and the stability safety factor of a model can be used to guide application of stabilized soil including calcined ginger nuts in engineering practice.